2008
DOI: 10.1007/s11427-008-0035-7
|View full text |Cite
|
Sign up to set email alerts
|

Construction of sperm-specific lactate dehydrogenase DNA vaccine and experimental study of its immunocontraceptive effect on mice

Abstract: Lactate dehydrogenase C4 (LDHC4) is a key enzyme for sperm metabolism. It is distributed specifically in testis and is highly immunogenic. In this study, two DNA vaccines pVAX1-hLDHC and pVAX1-mLDHC were constructed by inserting coding sequences of human and mice LDHC4 into the eukaryotic expression vector pVAX1. The production of LDHC4 specific antibodies was induced in the sera of vaccinated mice and the reproductive tract secretions of vaccinated female mice through immunization by mucosal surface instillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Detection of the proteins IZUMO1, LDHC, fertilin-b (ADAM2) and sperm flagellar protein (SPEF2) in this study presents an exciting finding as these antigens have all undergone degrees of assessment as immunocontraceptive vaccine targets (Chen et al 2008, Naz 2008, Wang et al 2009, Sun et al 2010, Khan et al 2011. Antibodies to adenylate kinase (AK8) and sperm protein 17 (SPA17) -proteins also identified presently -have been detected in sera of immunoinfertile men (Bhande & Naz 2007, Zhang et al 2007) and have also been suggested as potential antifertility targets.…”
Section: Study Of Stallion Sperm Proteome By Lc-ms/msmentioning
confidence: 66%
“…Detection of the proteins IZUMO1, LDHC, fertilin-b (ADAM2) and sperm flagellar protein (SPEF2) in this study presents an exciting finding as these antigens have all undergone degrees of assessment as immunocontraceptive vaccine targets (Chen et al 2008, Naz 2008, Wang et al 2009, Sun et al 2010, Khan et al 2011. Antibodies to adenylate kinase (AK8) and sperm protein 17 (SPA17) -proteins also identified presently -have been detected in sera of immunoinfertile men (Bhande & Naz 2007, Zhang et al 2007) and have also been suggested as potential antifertility targets.…”
Section: Study Of Stallion Sperm Proteome By Lc-ms/msmentioning
confidence: 66%
“…It is more heat stable, easy to produce and inexpensive [ 26 ]. The conformation and antigenicity of the antigenic protein encoded by DNA vaccines are identical to native antigen, and it has no potential pathogenicity [ 22 ]. In addition, it induces a long-lived humoral response, and the antibody has a greater avidity than protein-raised antibody [ 27 – 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another alternate possibility of generating an immune response against sperm proteins, in vivo, is to directly administer the sperm proteins to a host in which plasmid DNA encodes either individual or a collection of antigens. Later, several other sperm antigen-based DNA vaccines were investigated, such as LDHC4, 17 uroguanylin, 18 Izumo, 19 fertilin beta, 20 ZP3. 14 The first studies on DNA vaccination based upon sperm antigens YLP12 and FA-1 by Naz R.K. et al 15,16 showed that both Th1 and Th2 immune responses were induced after DNA vaccination, with a bias towards Th1 response.…”
Section: Introductionmentioning
confidence: 99%
“…The immunocontraceptive effects were long-lasting observed up to 1.3 years of the observation period and increased with time. Later, several other sperm antigen-based DNA vaccines were investigated, such as LDHC4, 17 uroguanylin, 18 Izumo, 19 fertilin beta, 20 ZP3. 21 In the present study, we have evaluated the immune responses in mice immunized with DNA construct encoding the mCRISP1 protein and compared them to the corresponding recombinant mCRISP1 protein.…”
Section: Introductionmentioning
confidence: 99%